A Biological Circuit Involving Mef2c, Mef2d, and Hdac9 Controls the Immunosuppressive Functions of CD4+Foxp3+ T-Regulatory Cells - Di Giorgio, Eros; Wang, Liqing; Xiong, Yan; Christensen, Lanette M.; Akimova, Tatiana; Han, Rongxiang; Samanta, Arabinda; Trevisanut, Matteo; Brancolini, Claudio; Beier, Ulf H.; Hancock, Wayne W. (Frontiers in Immunology, 2021)
The Mads/Mef2 (Mef2a/b/c/d) family of transcription factors (TFs) regulates differentiation of muscle cells, neurons and hematopoietic cells. By functioning in physiological feedback loops, Mef2 TFs promote the transcription of their repressor, Hdac9, thereby providing temporal control of Mef2-driven differentiation. Disruption of this feedback is associated with the development of various pathologic states, including cancer. Beside their direct involvement in oncogenesis, Mef2 TFs indirectly control tumor progression by regulating antitumor immunity. We recently reported that in CD4+CD25+Foxp3+ T-regulatory (Treg) cells, Mef2d is required for the acquisition of an effector Treg (eTreg) phenotype and for the activation of an epigenetic program that suppresses the anti-tumor immune responses of conventional T and B cells. We now report that as with Mef2d, the deletion of Mef2c in Tregs switches off the expression of Il10 and Icos and leads to enhanced antitumor immunity in syngeneic models of lung cancer. Mechanistically, Mef2c does not directly bind the regulatory elements of Icos and Il10, but its loss-of-function in Tregs induces the expression of the transcriptional repressor, Hdac9. As a consequence, Mef2d, the more abundant member of the Mef2 family, is converted by Hdac9 into a transcriptional repressor on these loci. This leads to the impairment of Treg suppressive properties in vivo and to enhanced anti-cancer immunity. These data further highlight the central role played by the Mef2/Hdac9 axis in the regulation of CD4+Foxp3+ Treg function and adds a new level of complexity to the analysis and study of Treg biology.